2016
DOI: 10.1002/adma.201504982
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Design of Mixed Matrix Membranes for Improved Gas Separation Performance

Abstract: High-performance metal-organic framework (MOF)/polyimide (PI) mixed matrix membranes (MMMs) are fabricated by a facile strategy by designing the MOF/PI matrix interface via poly dopamine coating. The overall separation performance of the designed MMMs surpasses the state-of-the-art 2008 Robeson upper bound for the H2 /CH4 and H2 /N2 gas pairs and approaches the 2008 upper bound for the O2 /N2 gas pair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
187
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 378 publications
(191 citation statements)
references
References 66 publications
3
187
0
1
Order By: Relevance
“…Mixed matrix membranes (MMMs), also called as organic‐inorganic hybrid membranes which combine the good film‐forming property of polymers with the superior gas separation performance of inorganic materials, have been widely studied as an alternative approach to break through the trade‐off phenomena of polymeric membranes in water treatment as well as gas separation . At present, zeolites, carbon nanotubes, metal oxide nanotubes, and graphene oxide (GO) are emerging as attractive candidates for the preparation and application of MMMs .…”
Section: Introductionmentioning
confidence: 99%
“…Mixed matrix membranes (MMMs), also called as organic‐inorganic hybrid membranes which combine the good film‐forming property of polymers with the superior gas separation performance of inorganic materials, have been widely studied as an alternative approach to break through the trade‐off phenomena of polymeric membranes in water treatment as well as gas separation . At present, zeolites, carbon nanotubes, metal oxide nanotubes, and graphene oxide (GO) are emerging as attractive candidates for the preparation and application of MMMs .…”
Section: Introductionmentioning
confidence: 99%
“…25 A recent study demonstrated that ZIF-8 nanoparticles coated with polydopamine (PD) enhanced their compatability with a Tröger's base derived polyimide matrix due to interactions by hydrogen bonding of the orthodihydroxyl groups in the PD and the nitrogen of the imidazole in ZIF-8. 26 The resulting MMMs demonstrated moderately improved gas separation properties but no propylene/propane permeation data were reported and the ZIF-8 content was limited to only 30 wt%.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, the contribution of the nanofillers to MMMs enhances the thermal stability of the membranes without considerable adverse effect on the processability of the membranes . Typical fillers used in these membranes include metal oxides, zeolites, two‐dimensional (2D) nanomaterials, covalent organic frameworks, and metal–organic frameworks (MOFs) . Although it has been observed that separation properties of polymeric membranes improve by adding inorganic fillers, there are still some technical challenges in the selection of proper polymer matrix and inorganic fillers.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Typical fillers used in these membranes include metal oxides, [23][24][25] zeolites, [26][27][28][29] two-dimensional (2D) nanomaterials, [30][31][32] covalent organic frameworks, [33][34][35] and metal-organic frameworks (MOFs). [36][37][38] Although it has been observed that separation properties of polymeric membranes improve by adding inorganic fillers, there are still some technical challenges in the selection of proper polymer matrix and inorganic fillers. Mostly, the poor filler dispersion and weak interfacial interactions of the polymer and fillers deteriorate the separation performance of the membranes.…”
Section: Introductionmentioning
confidence: 99%